Twin crane dispatching and scheduling algorithm - Luo, Yiming (2016)
This report aims to test the effects of a dispatching and scheduling algorithm on an end loading container terminal and determine the elements affecting the efficiency of the container terminal. This report provides basic knowledge on container shipment process and how container terminals operate. The scheduling algorithm is tested on a simulated real-life container terminal to determine various elements effecting terminal efficiency. Tests are done with moderations to each element separately, and all tests are run multiple times to avoid exceptions in results, the average value of all test results is used for comparison. By testing of the algorithm on the simulated container terminal, elements affecting terminal efficiency are isolated and ideal operating condition for the container terminal is determined. The result is limited by the complex environment of a real-time container terminal and the lack of details in simulation. This paper may help the analysis and efficiency optimization of end loading container terminals.